The Handbook of Service Innovation - Agarwal, Renu.; Agarwal, Renu.; Selen, Willem.; Selen, Willem.; Roos, Göran.; Roos, Göran.; Green, Roy.; Green, Roy. (Springer London : Imprint: Springer, 2015)
Bringing together some of the world’s leading thinkers, academics and professionals to provide practitioners, students and academicians with comprehensive insights into implementing effective service innovation. This book presents service innovation holistically and systemically across various service areas, including health, education, tourism, hospitality, telecommunications, and retail. It addresses contemporary issues through conceptual and applied contributions across industry, academia, and government, providing insights for improved practice and policy making. Featuring cutting-edge research contributions, practical examples, implementations and a select number of case studies across several growth service industries, this book also includes examples of failed service innovation attempts in order to demonstrate a balanced view of the topic and to make clear the pitfalls to be avoided. Culminating in a suggested step-by-step guide to enable service organization’s managers to understand and implement the concepts of service innovation and manage its evolutionary processes effectively, this book will prove a valuable resource to a wide reaching audience including researchers, practitioners, managers, and students who aspire to create a deeper scientific foundation for service design and engineering, service experience and marketing, and service management and innovation. Includes endorsements from professionals in the field of service innovation.